Derivation of Suitability Metrics for Remote Access Mode Experiments - Murray, S.; Lindsay, Euan; Lowe, D.; Tuttle, S. (Kassel University Press, 2010)
When considering the possible use of an online mode of experimentation it is important to evaluate the suitability of the remote access mode to a particular learning exercise. Within a large and diverse set of possible experiment-oriented learning exercises, it follows that not all laboratory experiments are well-suited for conversion to the remote access mode. In this paper we consider a range of factors that should be considered before the decision is taken to implement a remote laboratory. These factors fit broadly into four categories: learning factors, equipment factors, cohort factors and accreditation factors. Some of the factors may demonstrate a tendency to belong to more than one category, and some may present with a more significant weighting than others, but the categorical organization of the factors adds an ability to apply an objective assessment to remote access mode suitability.